The Influence of the Quantum Learning Model on Critical Thinking Skills of Grade VII Students in Social Science Learning at SMPN 5 Sidoarjo - Keshia Zahira (Jurnal Dialektika Pendidikan IPS, 2026)
Social studies learning at SMPN 5 Sidoarjo often uses concept maps. Opportunities for optimizing the application of innovative learning models are still wide open so the purpose of this study was to determine the effect of the quantum learning model on the critical thinking skills of grade VII students in social studies learning at SMPN 5 Sidoarjo in the 2025/2026 academic year. This study used a pretest posttest control group method with a non equivalent type where the experimental class was not selected randomly with the aim of creating a comparison that produced changes after being given treatment. Data analysis techniques used in this study were normality tests, homogeneity tests, n-gain tests and hypothesis teste. The result of showed that the average n-gain value of the experimental class was 0.549, which means that the quantum learning model was considered quite effective in improving the critical thinking skills of grade VII students at SMPN 5 Sidoarjo. The result of hypothesis testing using independent sample t-test showed a sig value of 0.000 smaller than 0.05. The results and discussion of the study inicate a significant difference between the pretest and posttest, thus proving that the application of the quantum learning model is able to provide a positive influence on the critical thinking skills of grade VII students in social studies learning at SMPN 5 Sidoarjo. This finding states that H0 is rejected and H1 is accepted so the application of the quantum learning model is an alternative learning model that is fun and able to improve students critical thinking skills.